Decolonizing English Language Teaching in Colombia: Epistemological Perspectives and Discursive Alternatives - Fandiño-Parra, Yamith José (Colombian Applied Linguistics Journal, 2021)
In times of geocultural subalternization of knowledge and education, English language teaching (ELT) is torn between subalternizing policies and subjectivating practices. Within this context, ELT teacher educators face policies and discourses aimed at framing their teaching practices, professional lives, and research agendas. However, at the same time, they are expected to engage in practices and processes that allow for personal adaptation and social change. Amid this ambivalence, this reflection paper makes a call to decolonize ELT in Colombia. To this effect, this paper reviews some basic epistemological perspectives such as colonialism and decolonial studies. Then, it proposes the decolonization of ELT, along with a grammar of decoloniality based on discursive alternatives about power, knowledge, and being with the potential of bringing about a transformative teacher subjectivation. The main conclusion is that the Colombian ELT community needs to first deconstruct dominant structures and strategies that enact epistemic and cultural dominance of the global north, and then construct alternative discourses and practices that acknowledge and disseminate the singularities of its knowledge and culture.